Wealth through Integration Regional Integration and Poverty-Reduction Strategies in West Africa - Ayuk, Elias T.; Kaboré, Samuel T.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Could regional integration be a first step toward joining the global market? In a context where liberalizing trade has not produced the expected gains in developing countries and growth in global trade has not led to the expected  economic growth, an alternative solution has emerged. This new paradigm  suggests that  trade liberalization should be accompanied by public investment. However, by its  very nature, trade liberalization leads to a reduction in revenues from duties and taxes, which means that the available resources for  public investments will also be reduced. There are now solid arguments for encouraging the less-developed countries to first emphasize regional integration before trying to access the global market. This book explores the issues linked to regional integration in West Africa and presents empirical data about  the experiences in = West African Economic and Monetary Union (WAEMU) countries to converge their economies. It also examines how these efforts, which make a major contribution to regional integration, influence poverty reduction in the economic and monetary community.  It will be of interest to  researchers working in this area.    .
INTRODUCTION: WHY INTEGRATE? -- CHAPTER 1: FIFTEEN YEARS OF WAEMU: RESULTS AND STRATEGIES FOR THE FUTURE -- DIERY SECK CHAPTER 2. GROWTH AND CONVERGENCE IN AFRICA:  A DYNAMIC PANEL APPROACH -- CHAPTER 3: HAS THERE BEEN REAL AND STRUCTURAL CONVERGENCE IN WAEMU COUNTRIES?-. CHAPTER 4 THE IMPACT OF THE CONVERGENCE, STABILITY AND GROWTH PACT IN THE WAEMU -- CHAPTER 5: REAL CONVERGENCE IN THE WAEMU AREA: A BAYESIAN ANALYSIS -- CHAPTER 6: THE EFFECTS OF CREDIT CONSTRAINTS ON ECONOMIC CONVERGENCE: THE CASE OF THE WAEMU COUNTRIES -- CHAPTER 7: FREE MOVEMENT OF GOODS IN WAEMU COMMUNITY LAW AND THE EUROPEAN UNION: A COMPARATIVE STUDY FROM THE PERSPECTIVE OF TRADE -- CHAPTER 8: THE ROLE OF CASH TRANSFERS FROM MIGRANTS IN PROMOTING THE FINANCING OF ECONOMIC DEVELOPMENT IN WAEMU COUNTRIES -- CHAPTER 9: EFFICIENCY OF CREDIT THAT TARGETS THE POOR: MEASURES AND APPLICATION OF AGRICULTURAL CREDIT IN BURKINA FASO -- CHAPTER 10: PERFORMANCE AND EFFECTIVENESS OF THE DECENTRALISED FINANCIAL SYSTEM AND POVERTY REDUCTION IN NIG -- CHAPTER 11: FINANCING FARMING AND THE FOOD CRISIS IN AFRICA: WHAT ROLE CAN MICRO-FINANCE PLAY? -- CHAPTER 12: COMMON EXTERNAL TARIFF (CET) AND TARGETING THE POOR IN MALI -- CHAPTER 13: HOW DOES COMMUNICATION ENRICH INTEGRATION POLICIES -- CHAPTER 14: CONCLUSIONS AND PERSPECTIVES: CREATING WEALTH FROM INTEGRATION .
Keywords: Development economics; Economic growth; Economic policy; Development Economics; Economic Growth; Economic Policy